Women’s perspective on the assistance received during the parturition process (Research, Society and Development, 2021)
Aims to know the women’s perspective on the assistance received during the parturition process. The research used a qualitative method lead by the COREQ protocol. The data collection was executed by an unstructured, individual, and a recorded interview with eight puerperal women who attended Tangará da Serra county, state of Mato Grosso. The corpus was systematized from the content analysis and the findings were understood by literature review. Two categories were developed from the analytic process: (a) The parturition construction: moments that precede it and their characteristics; (b) Experienced perceptions during the postpartum. It was identified dehumanizing aspects in obstetric care, as women wandered during the labor between two distinct health services in the county, the predominance of cesarean birth, as well as the non-compliance with the Companion Law. In this paper became evident that in this county the assistance provided for women during the delivery process is lower than the recommendation contributed by the Ministério da Saúde for the parturition process.